Hiring High-Skilled Labor Through Mergers and Acquisitions - Chen, Jun; Hshieh, Shenje; Zhang, Feng (Journal of Financial and Quantitative Analysis, 2024)
Using random H-1B visa lotteries as a natural experiment, we find that firms respond to shortages of high-skilled workers by acquiring firms that employ such workers. The effect is stronger among firms with high human capital and more senior workforces, firms facing tight labor markets and legal barriers to poaching workers, and firms lacking foreign affiliates. The acquired workers are highly educated, sharing skills and occupations similar to those of the acquirer’s existing workers. Our findings suggest skilled labor is an important driver of acquisitions and acquiring is an effective means of obtaining skilled labor.